"A smile on everybody's face": A multiple case study of community ukulele groups. (August 2018) - Giebelhausen, Robin; Kruse, Adam J.
The purpose of this study was to explore educational and social environments of multiple American community ukulele groups. The foundations, objectives, and leadership of four community ukulele groups offer expansions to our understandings of the ways in which people are teaching and learning with the ukulele as well as what are hopefully valuable considerations for music educators. This study helps to support the notion that there is no singular experience nor ubiquitous practice for community ukulele groups, though some important values (e.g., fun) might be common. In this study, the group leaders established learning environments that were largely participatory, and while the leadership itself may not have always been democratic, the leaders' choices were reflective of the group members' interests and goals. Considerations include prioritizing fun, questioning presentational performance, and considering leadership styles and the role of leadership in a responsive educational environment.